2020
DOI: 10.1080/17453674.2020.1832304
|View full text |Cite
|
Sign up to set email alerts
|

Which Oxford Knee Score level represents a satisfactory symptom state after undergoing a total knee replacement?

Abstract: Background and purpose — Meaningful interpretation of postoperative Oxford Knee Score (OKS) levels is challenging. We established Patient Acceptable Symptoms State (PASS) and Treatment Failure (TF) values for the OKS in patients undergoing primary total knee replacement (TKR) in Denmark. Patients and methods — Data from patients undergoing primary TKR between February 2015 and January 2019 was extracted from the arthroplasty registry at the Copenhagen University Hospital, Hvidovre in Denmark. Data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Second, we demonstrated how the adjusted predictive modeling method altered the cut-offs as the proportion of patients being importantly improved, feeling satisfactory symptoms, or feeling treatment failure differed greatly from 50% ( 18 ). These findings align with previous studies, and emphasize the preference of the predictive modelling method above the ROC method ( 12 , 13 , 16 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Second, we demonstrated how the adjusted predictive modeling method altered the cut-offs as the proportion of patients being importantly improved, feeling satisfactory symptoms, or feeling treatment failure differed greatly from 50% ( 18 ). These findings align with previous studies, and emphasize the preference of the predictive modelling method above the ROC method ( 12 , 13 , 16 ).…”
Section: Discussionsupporting
confidence: 92%
“…The large difference could be explained by the ROC analysis used on a population where the proportion improved was very high (92.7%), possibly causing an upward biased value in the comparative study ( 11 ). However, our adjusted OKS PASS and TF values found at 3 and 12 months postoperatively are within 3 points of the proposed cut-offs previously suggested in a study using the same method for patients undergoing TKA ( 13 ). These findings suggest that the OKS PASS and TF scores are similar in patients undergoing UKA and TKA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The PASS at one-year follow-up was defined as an OKS above 30. 30 Any p-values less than 0.05 were considered statistically significant. All statistics were calculated using R v. 3.6.0 (R Foundation for Statistical Computing, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…Total scores range from 12 points (best) to 60 points (worst). Many scholars eventually suggested that these scores be adjusted to range from 0–4, with a maximum possible score of 48 [ 18 ]. Accordingly, the latest revised OKS scoring system rates each item from 0–4, with total possible scores ranging from 0 (worst) to 48 (best).…”
Section: Methodsmentioning
confidence: 99%